Association between blood lead and sociodemographic parameters among children - Rojas, Maritza; Espinosa, C; Seijas, D (Revista de Saúde Pública, 2003)
OBJECTIVE: To determine the relationship between blood lead concentration (Pb-S), and sociodemographic parameters among children. METHODS: Blood lead concentration (Pb-S) was determined in 243 children (aged 5.94±2.78 years) in the district of Valencia. The required analysis was performed at the Center for Toxicological Investigations of University of Carabobo (CITUC), Venezuela, between January 1st, 1998 to December 31st, 2000. Geographical Information Systems (GIS) technology was used for data mapping. RESULTS: Average Pb-S (11.62 ug/dl) was significantly higher than the allowed levels. One hundred and fifty (61.7%) children had Pb-S levels above the allowed concentration (VSLP) and this amount was significantly high in relation to the total number of subjects studied. The logistic regression analysis showed a significant association of sectors 12 (status A) and 16 and 28 (status C) with VSLP (R=0.1189; p